2010
DOI: 10.1542/peds.2009-1906
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Goat's Milk for Infants: Myths and Realities—A Review

Abstract: Many infants are exclusively fed unmodified goat's milk as a result of cultural beliefs as well as exposure to false online information. Anecdotal reports have described a host of morbidities associated with that practice, including severe electrolyte abnormalities, metabolic acidosis, megaloblastic anemia, allergic reactions including life-threatening anaphylactic shock, hemolytic uremic syndrome, and infections. We describe here an infant who was fed raw goat's milk and sustained intracranial infarctions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…Commercial sale and/or distribution of raw milk varies among different countries. Nevertheless, unpasteurized dairy products have gained popularity by consumers who say raw milk strengthens the immune system and provides other health benefits, although it is proven that raw goat's milk is a vehicle for pathogen transmission [43]. Toxoplasmosis transmission by unpasteurized milk can represent a significant means of contamination by this agent [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Commercial sale and/or distribution of raw milk varies among different countries. Nevertheless, unpasteurized dairy products have gained popularity by consumers who say raw milk strengthens the immune system and provides other health benefits, although it is proven that raw goat's milk is a vehicle for pathogen transmission [43]. Toxoplasmosis transmission by unpasteurized milk can represent a significant means of contamination by this agent [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have been published on infants who were fed homemade goat milk formulas and then were diagnosed with megaloblastic anemia caused by folate and or vitamin B 12 deficiency (Ziegler et al, 2005). Basnet et al (2010) reported a case where an infant was exclusively fed goat milk, which led to azotemia (abnormally high levels of nitrogen compounds in the blood), hypernatremia (electrolyte imbalance caused by elevated sodium levels) and hemorrhages in the brain. This was caused by the high levels of sodium in goat milk compared to human milk.…”
Section: Effect On Infancy Intakementioning
confidence: 99%
“…A renal tubular acidosis was initially part of their differential diagnosis [2]. In addition, a 5-month-old boy fed with raw goat's milk since the age of approximately 4 months developed intracranial infarctions in the setting of severe hypernatremia and azotemia; the patient had increased anion gap metabolic acidosis [3]. Finally, two cases of undiluted goat's milk consumption mimicking metabolic diseases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Goat's milk contains between 3.56 g of protein and 50 mg of sodium per 100 mL (22 mmol/L), which is approximately three times that of human milk (1.03 g and 17 mg per 100 mL) [3]. There is also 242 mg of potassium (62 mmol/L) and 202 mg of chloride (57 mmol/L) per 100 mL [1].…”
Section: Discussionmentioning
confidence: 99%